Understanding the activity of carbon-based single-atom electrocatalysts from ab initio simulations - Zhong, Lixiang (2023)
Heterogeneous single-atom catalysis has attracted great research interest in recent years. The atomically dispersed metal atoms, which are generally active sites in single-atom catalysts, could result in unconventional reaction mechanisms due to the site confinement of reaction intermediates. Their coordination environments substantially affect their activities through tuning the adsorption of reaction intermediates. Two kinds of coordination effects were discussed here: intrinsic coordination and dynamic coordination. The intrinsic coordination is formed in the synthesis process of the catalyst, and the dynamic coordination refers to the in situ coordination of an atom or a group introduced during catalysis. The charge capacity of the active site and solvation effect also play an important role in the adsorption of reactants and intermediates on single-atom catalysts.